Outsourcing Employee Recruitment And Selection Process - Kania Laelawati; Imas Komariyah (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
The impact of the recruitment and selection procedure on the performance of outsourced employees at Paskal Hyper Square Bandung has been studied. According to the findings of the study, the recruiting and selection processes have a favorable and significant effect on the performance of outsourced employees at Paskal Hyper Square Bandung, with recruitment being the most influential variable. Recruitment variables have a favorable and significant impact on outsourced employees' performance at Paskal Hyper Square Bandung